2017
DOI: 10.4236/ajcc.2017.62018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vegetation Productivity in the Northern Part of Nigeria

Abstract: Climate change is one of the greatest threats facing the global community and has been mainly induced by increasing atmospheric concentrations of greenhouse gases resulting from fossil fuel energy use and change in vegetation cover. This study used modelling techniques to determine how changes in climate could affect vegetation productivity in the northern part of Nigeria. Climatic parameters (Rainfall, Minimum and Maximum Temperatures) as well as coarse Normalised Difference Vegetation Index (NDVI) data for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, the NDVI is a general and most extensively used index (e.g. Eastman & Fulk, 1993;Millington et al, 1994;Chen, 1996;Mas, 1999;Anyamba et al, 2001;Lu et al, 2004;Drissi et al, 2009;Yelwa & Eniolorunda 2012;Bhunia & Shit, 2013;Xue & Su, 2017;Yelwa & Usman, 2017;Yelwa et al, 2019;Abdullahi & Yelwa, 2020).…”
Section: Satelite-based Vegetation Indices Used In Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the NDVI is a general and most extensively used index (e.g. Eastman & Fulk, 1993;Millington et al, 1994;Chen, 1996;Mas, 1999;Anyamba et al, 2001;Lu et al, 2004;Drissi et al, 2009;Yelwa & Eniolorunda 2012;Bhunia & Shit, 2013;Xue & Su, 2017;Yelwa & Usman, 2017;Yelwa et al, 2019;Abdullahi & Yelwa, 2020).…”
Section: Satelite-based Vegetation Indices Used In Related Studiesmentioning
confidence: 99%
“…This is because it has been experimented successfully in environmental remote sensing analysis for data transformation, information compression, and change detection studies. When PCA is used with standardised principal components in a geographical information systems (GIS) environment, it indicated clearly that the major element of variability is that which occurs spatially (Singh & Harrison, 1985;Eastman & Fulk, 1993;Anyamba et al, 2001;Bhunia & Shit, 2013;Yelwa & Usman, 2017;Yelwa et al, 2019). PCA normally allows any set of original satellite imageries to be transformed to a set of new images (referred to as components) where such component images contain all of the information in the original images entered into such time-series are uncorrelated with one another (Richards, 1984).…”
Section: Satelite-based Vegetation Indices Used In Related Studiesmentioning
confidence: 99%
“…They found that it is possible to apply Co-Kriging to determine how climatic variation can change the vegetation in the northern part of Nigeria. [27] identified that geostatistical techniques are methods appropriate to assed the vegetation productivity in the northern part of Nigeria. They used modelling techniques to determine how changes in climate could affect vegetation productivity in the northern part of Nigeria.…”
Section: Introductionmentioning
confidence: 99%